HUBUNGAN IMBALAN FINANSIAL DAN IMBALAN NON FINANSIAL DENGAN KINERJA KARYAWAN PT INDOSAT TBK-MEDAN - Muhammad Pradhana Budi Kurnia Nasution; Lusy Anna (Universitas Sumatera Utara, 2013)
ABSTRACTThe purpose of this study is to find out the relationship between the financial compensation and nonfinancial compensation toward employee performance in PT Indosat Tbk – Medan.The population in this study is 123 of PT Indosat Tbk – Medan employees. Sampling method in this study uses Slovin formula to produce 55 samples of PT Indosat Tbk – Medan employees. The kind of datas collected and used are primary data and secondary data by using the techniques of data collection through the dissemination of the questionnaire, interview, and study documentation.The result of this study indicates that there is positive and significant relationship between financial compensation and nonfinancial compensation toward employee performance. Pearson correlation method indicates that the relationship of nonfinancial compensation is stronger than financial compensation toward employee performance.The t test indicates that the variable of nonfinancial compensation contributes stronger in improving employee performance, it is proven by nonfinancial compensation correlation coefficient (r) toward performance is 0,626 which is the relation between the two variables strong and more dominant.Key Words :Financial Compensation, NonFinancial Compensation, andPerformance